Effect of Respiratory Relaxation Techniques on Pain Adaptation in Maternity Mothers at RSU Royal Prima in 2020 - Wang Chunxiang; Florenly Florenly; Liena Liena; Dewi Riastawaty Purba (Budapest International Research in Exact Sciences (BirEx) Journal, 2022)
Every year an estimated 529,000 women die as a result of complications arising from pregnancy and childbirth. Labor pain is a physiological condition, an unpleasant feeling that occurs during labor. Nonpharmacological pain management can increase satisfaction during labor because the patient can control his feelings and strength, one of which is the texture of respiratory relaxation. The purpose of this study was to find out the effect of respiratory relaxation techniques on pain adaptation in maternity mothers. This type of research is descriptively correlational, using the One Group Pretest-Postest approach. Location in RSU Royal Prima Jalan Ayahanda Number 68A, Sei Putih Tengah, Medan Petisah, North Sumatra, september - November 2020. The population of 43 people, determining the number of samples with the formula slovin, so that the sample was obtained as many as 30 people. The data analysis used is a normality test using the Shapiro Wilk test, because the number of samples is <50. Bivariate analysis of the data is distributed normally using an at-dependent test (paired t-test), while if the data is not distributed normally using the Wilcoxon Signed Rank Test, with a meaningful limit of <0.05. The results of the study score change in the level of pain Wilcoxon test results at the time of the pre-test test the result of a mean value of 3,466, at the time of the post-test test the mean value of 3,166. So the result of the value Z = -2,714 then p-value as much as 0.007<0.05 so that it is concluded ho rejected and Ha received, which means there is an effect of giving respiratory relaxation techniques to changes in pain in maternity mothers when-I at RSU Royal Prima in 2020.